Reef Shark Science – Key Questions and Future Directions - Heupel, Michelle R.; Papastamatiou, Yannis P.; Espinoza, Mario; Green, Madeline E.; Simpfendorfer, Colin A. (Frontiers in Marine Science, 2019)
The occurrence of sharks on coral reefs has been well documented for decades, especially since the advent of SCUBA diving. Despite this, it is only within the last decade that substantial research effort has been directed at these species. Research effort has increased in conjunction with the realisation that reef shark populations have experienced significant declines throughout their distribution. However, trends in declines have been coupled with reports of high abundance in some areas providing confusion about what healthy reef shark populations should look like. Given that coral reefs are among the most biologically diverse and productive habitats, but also are one of the most threatened by climate change due to the effects of rising temperature and declining pH, there is a need to understand reef sharks to better predict consequences for their populations. Studies of reef sharks also have the potential to provide insights into the functioning of their populations and ecosystems more broadly because of the spatially constrained nature of their distributions, and high water visibility in most locations. These aspects make studying reef shark populations integral to understanding coral reef ecosystem dynamics and resilience to pressures. This paper synthesises a number of key questions about coral reef sharks based on our experience researching this group of species over the past decade. Key research gaps and critical questions include aspects of life history, population dynamics, ecology, behaviour, physiology, energetics, and more. This synthesis also considers the methods used to date, and what new and emerging techniques may be available to improve our understanding of reef shark populations. The synthesis will highlight how even basic questions relating to reef shark population sizes, how large they should be, and what impacts do they have on reef ecosystems, remain either unanswered or highly controversial.